Pengaruh Model Pembelajaran Integratif Berbasis Kearifan Lokal Terhadap Karakter Bernalar Kritis Siswa Kelas IV - Ramdini, Distian Fisti; Nugroho, Wahyu; Puspasari, Yovita (Education and Development Research, 2024)
Abstract: This study aims to determine the extent of the differences between students who are given the application of integrative learning models based on Javanese local wisdom in the learning process and students who still use conventional learning models on students' critical reasoning characters. This research uses quantitative methods. The form of design in this research is quasi-experimental research. This research was conducted by applying certain treatments to one group (experimental group) and not applying them to another group (control group), in which the two groups were pre-tested and post-tested. Furthermore, the data were analyzed using the t-test using the paired sample t-test and the independent sample t-test with the results of the two hypothesis tests being a (2-tailed) value of 0.000 less than 0.05, then Ha was accepted and H0 was rejected. It can be concluded that the research results show differences in students' critical reasoning characters in the experimental class were higher than the control class. So from this study, an integrative learning model based on Javanese local wisdom has an effect on increasing the critical reasoning character of fourth grade elementary school students. Abstrak: Penelitian ini bertujuan untuk mengetahui sejauh mana perbedaan antara siswa yang diberikan penerapan model pembelajaran integratif berbasis kearifan lokal jawa pada proses pembelajaran dengan siswa yang masih menggunakan model pembelajaran konvensional terhadap karakter bernalar kritis siswa. Penelitian ini menggunakan metode kuantitatif. Bentuk desain dalam penelitian ini ialah penelitian eksperimen semu (quasi experiment). Penelitian ini dilakukan dengan cara menerapkan treatment tertentu pada satu kelompok (kelompok eksperimen) dan tidak menerapkannya pada kelompok yang lain (kelompok kontrol), yang mana dua kelompok tersebut dilakukan pre test dan post test. Selanjutnya data dianalisis dengan uji t menggunakan paired sample t-test dan independent sample t-test dengan hasil kedua uji hipotesis tersebut adalah nilai (2-tailed) sebesar 0,000 kurang dari 0,05, maka Ha diterima dan H0 ditolak, dapat disimpulkan hasil penelitian menunjukkan perbedaan karakter bernalar kritis siswa pada kelas eksperimen lebih tinggi daripada kelas kontrol. Sehingga dari penelitian ini, model pembelajaran integratif berbasis kearifan lokal jawa berpengaruh terhadap peningkatan karakter bernalar kritis siswa kelas IV Sekolah Dasar.